180 Jr. Platform Speaker: Evaluation of Phase-Feeding Strategies and Lysine Specifications for Grow-Finish Pigs. - Menegat, M (J Anim Sci, 2018)
Phase-feeding programs have been used to closely meet the nutrient requirements of grow-finish pigs and reduce nutrient excretion in the environment. However, previous studies suggest that simplification of feeding strategies to fewer phases can maximize growth performance and carcass characteristics while being more practical from a logistical standpoint. Therefore, three studies were conducted to evaluate phase-feeding strategies for grow-finish pigs under commercial research conditions. As the core component of developing feeding strategies is setting dietary lysine, the studies also evaluated lysine specifications. Experiments were conducted with approximately 1,100 pigs (PIC 359 × 1050) per experiment from 27–127 kg BW and 25–27 pigs per pen. Experiment 1 evaluated a 4-phase program with lysine specifications for maximum growth as recommended by the genetic company; a 4-phase program with lysine for optimal income over feed cost (IOFC); a 4-phase program with lysine for optimal IOFC in early finishing and maximum growth in late finishing; and a 2-phase program with lysine for maximum growth. Interestingly, all programs resulted in similar IOFC. Moreover, the 2- or 4-phase programs resulted in similar growth performance and carcass characteristics. In light of this, the following experiments evaluated feeding programs with 1, 2, 3, or 4 phases. Lysine specifications for 100% or 98.5% of maximum growth were used in Exp. 2 and 3, respectively. The 1-phase program compromised growth performance in both studies. Feeding lysine levels for maximum growth in either 2- or 4-phase program resulted in similar growth performance, carcass characteristics, and IOFC (Exp. 2). However, feed efficiency and IOFC were compromised in the 2-phase program when lysine levels were slightly below the recommendation for maximum growth (Exp. 3). The studies performed by our group suggest that simplification of feeding programs for grow-finish pigs can be implemented provided that lysine is closely set to the requirements.